Development of Student Worksheets based on Project-Based Learning on Renewable Energy to Improve Students' Concept Mastery and Creative Thinking Skills in Senior High School - Revista Rizky Rahmanniar; Edi Supriana; Endang Purwaningsih (Berkala Ilmiah Pendidikan Fisika, 2024)
The student worksheets development activity was carried out because its use in learning was still relatively simple, thus influencing students' enthusiasm for mastering concepts and developing creative thinking skills. This is due to limited teacher innovation in developing teaching materials that suit student needs. This research aims to determine the feasibility of project-based student worksheets learning and its influence on mastery and creative thinking skills. The feasibility of Projrct-based Learning (PjBL)-based worksheets learning was measured using the validation results of media experts, teaching module experts, and field practice experts, with scores of 78.45%, 86.11%, and 92.70%, respectively. Mastery of concepts and creative thinking abilities were measured using the Independent Sample T-test based on pretest and post-test data. The implementation results show an increase in mastery of concepts and creative thinking skills in classes that implement PjBL-based worksheets compared to classes that do not implement PjBL-based worksheets. The values are 0.003 and 0.032, respectively (significance level <0.05).